Efficacy of Cognitive Behaviour Therapy on Reducing Maladaptive Behaviour among Students Enrolled in Counselling, Psychology and Sociology of Education (EPSE) - Egenti, Dr. Nkechi T.; Ncheke, Dr. Damian C.; Umah, Dr. Sunday S.; Egwim, Chisom Ezinne; Uzoagba, Ngozi; De. Lilian C. , Ozoemena (Journal of Advanced Psychology, 2021)
Purpose: The study investigated the efficacy of cognitive behaviour therapy (CBT) in the reduction of on maladaptive behaviour of undergraduate students. The purpose for the study came as a result of the increasing rate of maladaptive behaviour to which the researchers sought to find solutions. Pre-test-post-test randomized control trial experimental design was adopted by the researchers for the study. Methodology: Sixty-four (64) maladaptive undergraduate students who were drawn through proportionate stratified random sampling technique constituted the sample for the study. The maladaptive students were randomly assigned to experimental (34) and control (30) groups. Maladaptive Assessment Scale for Students (MASS) and Maladaptive Behaviour Scale (MBS) were used for data collection. MASS and MBS were properly validated by experts in test development and the internal consistency reliability indices of the items estimated as 0.79 and 0.81 respectively using cronbach alpha method. Before the commencement of the testing and treatment package, the researchers assured the participants of confidentiality of interactions and personal information as they work together in self-disclosure. Thereafter, pre-treatment assessment (pre-test) was conducted using the MASS and MBS in order to collect baseline data (Time 1). After that, the experimental group was exposed to 90 minutes of the CBT programme twice a week for a period of 6 weeks. The treatment took place between September and November 2019. Post-test (Time 2) assessment was conducted 1 week after the last treatment (Time 3). Data collected were analyzed using repeated measures analysis of variance. Results: The findings of the study revealed that the effect of cognitive behavioural therapy on reducing the maladaptive behaviour of undergraduate students was significant at post-test and follow-up measures. One of the contributions of the findings is that if undergraduate students are not properly counselled, their maladaptive behaviours will continue to increase. Unique contribution to theory, policy and practice: Based on the findings, it was recommended among others that Federal Government or relevant education authorities should provide enough guidance counsellors in the various institutions of higher learning who will assist in the counselling of the students on the dangers of maladaptive behaviours using CBT. It is also recommended that counselors, psychologists among others should adopt cognitive behavioural therapy for handling maladaptive behaviour.